Evaluating vulnerability of Central Asian water resources under uncertain climate and development conditions: The case of the Ili‐Balkhash Basin - de Boer, T.; Paltan, H.; Sternberg, T.; Wheeler, K. (Water, 2021)
The Ili-Balkhash basin (IBB) is considered a key region for agricultural development and international transport as part of China’s Belt and Road Initiative (BRI). The IBB is exemplary for the combined challenge of climate change and shifts in water supply and demand in transboundary Central Asian closed basins. To quantify future vulnerability of the IBB to these changes, we employ a scenario-neutral bottom-up approach with a coupled hydrological-water resource modelling setup on the RiverWare modelling platform. This study focuses on reliability of environmental flows under historical hydro-climatic variability, future hydro-climatic change and upstream water demand development. The results suggest that the IBB is historically vulnerable to environmental shortages, and any increase in water consumption will increase frequency and intensity of shortages. Increases in precipitation and temperature improve reliability of flows downstream, along with water demand reductions upstream and downstream. Of the demand scenarios assessed, extensive water saving is most robust to climate change. However, the results emphasize the competition for water resources among up- and downstream users and between sectors in the lower Ili, underlining the importance of transboundary water management to mitigate cross-border impacts. The modelling tool and outcomes may aid decision-making under the uncertain future in the basin.